THE MALE GAZE: SEXUAL OBJECTIFICATION ON WOMEN’S BODY IN THE SUBSTANCE, A MOVIE SCRIPT BY CORALIE FARGEAT - Melania Priska Mendrofa; Bernice Jovetta Suryadi (LINGUA LITERA : journal of english linguistics and literature, 2026)
This study examines how The Substance portrays the sexual objectification of women’s bodies through the framework of the male gaze, with the aim of understanding how media representations contribute to the psychological of women. The research is grounded in concerns that women are often reduced to visual objects, valued more for appearance than identity or capability. A qualitative method is employed, drawing on Fredrickson and Roberts’ (1997) Sexual Objectification Theory to analyze key concepts such as male gaze, body shame, and anxiety. The analysis is conducted through close reading of dialogues, visual scenes, and character behavior, allowing for the identification of how the masculine perspective in media narratives fosters internalized objectification. Findings reveal that the female protagonist, Elisabeth Sparkle, is consistently depicted through a fragmented and sexualized lens that reinforces patriarchal ideologies. This portrayal leads her to internalize objectification, resulting in psychological consequences including anxiety, shame, and a fractured sense of self. The study concludes that The Substance illustrates how women who fail to conform to imposed ideals are systematically marginalized or replaced, underscoring the need for critical scrutiny of gendered visual narratives in contemporary media.